Amendments and frames: The Women Making History movement and Malmö migration history. Issue 2 (1st October 2018) - Björgvinsson, Erling; Høg Hansen, Anders
This article explores existing and emerging frames of writing history involving a push for new modes of telling and writing history/histories. This, from the point of view of a recent movement, in short named Women Making History, launched in Malmö, Sweden in 2013 aiming to cover a 100-year period, from when immigration began until the present day. The movement ‐ engaged in activism and archival work and research around the lives and work of women immigrants in the city ‐ took off in 2013 with support from authors engaged in a Living Archives1 research project, and formally ended, though some activity continues, with a book publication in 2016. In collaboration with the movement Feminist Dialogue Malmö University researchers (mainly the two authors and students) have been documenting activities and workshops over three years, revealing the voicing of ambivalent identities that wish to maintain a plurality and openness of identifications and directions. These voices do not want to be framed as 'outsiders', 'homogenized others' or 'victimized strangers', and struggle with a feeling of being amended to a more homogenous national history ‐ an ambiguous predicament which is investigated in this article through diverse ways of trying to understand how belonging is developed in the notions of multidirectionality, multi-logues, amendments and re/framing.